A Novel Rice Quality Assessment Kit - CGIAR Research Program on Rice (2019)
The IRRI Rice Quality Assessment Kit is available in the second half of 2019 from GrainPro Inc.; several of the kits have already been purchased by millers and other value chain actors to help them in their daily tasks too. There is a continuous flow of inquiries for the kit.